Antisense oligonucleotides targeting apolipoprotein(a) in people with raised lipoprotein(a): two randomised, double-blind, placebo-controlled, dose-ranging trials. Issue 10057 (5th November 2016) - Viney, Nicholas J; van Capelleveen, Julian C; Geary, Richard S; Xia, Shuting; Tami, Joseph A; Yu, Rosie Z; Marcovina, Santica M; Hughes, Steven G; Graham, Mark J; Crooke, Rosanne M; Crooke, Stanley T; Witztum, Joseph L; et al.
Summary: Background: Elevated lipoprotein(a) (Lp[a]) is a highly prevalent (around 20% of people) genetic risk factor for cardiovascular disease and calcific aortic valve stenosis, but no approved specific therapy exists to substantially lower Lp(a) concentrations. We aimed to assess the efficacy, safety, and tolerability of two unique antisense oligonucleotides designed to lower Lp(a) concentrations. Methods: We did two randomised, double-blind, placebo-controlled trials. In a phase 2 trial (done in 13 study centres in Canada, the Netherlands, Germany, Denmark, and the UK), we assessed the effect of IONIS-APO(a)Rx, an oligonucleotide targeting apolipoprotein(a). Participants with elevated Lp(a) concentrations (125–437 nmol/L in cohort A; ≥438 nmol/L in cohort B) were randomly assigned (in a 1:1 ratio in cohort A and in a 4:1 ratio in cohort B) with an interactive response system to escalating-dose subcutaneous IONIS-APO(a)Rx (100 mg, 200 mg, and then 300 mg, once a week for 4 weeks each) or injections of saline placebo, once a week, for 12 weeks. Primary endpoints were mean percentage change in fasting plasma Lp(a) concentration at day 85 or 99 in the per-protocol population (participants who received more than six doses of study drug) and safety and tolerability in the safety population. In a phase 1/2a first-in-man trial, we assessed the effect of IONIS-APO(a)-LRx, a ligand-conjugated antisense oligonucleotide designed to be highly and selectively taken up by hepatocytes, at the BioPharma Services phase 1 unit (Toronto, ON, Canada). Healthy volunteers (Lp[a] ≥75 nmol/L) were randomly assigned to receive a single dose of 10–120 mg IONIS-APO(a)LRx subcutaneously in an ascending-dose design or placebo (in a 3:1 ratio; single-ascending-dose phase), or multiple doses of 10 mg, 20 mg, or 40 mg IONIS-APO(a)LRx subcutaneously in an ascending-dose design or placebo (in an 8:2 ratio) at day 1, 3, 5, 8, 15, and 22 (multiple-ascending-dose phase). Primary endpoints were mean percentage change in fasting plasma Lp(a) concentration, safety, and tolerability at day 30 in the single-ascending-dose phase and day 36 in the multiple-ascending-dose phase in participants who were randomised and received at least one dose of study drug. In both trials, the randomised allocation sequence was generated by Ionis Biometrics or external vendor with a permuted-block randomisation method. Participants, investigators, sponsor personnel, and clinical research organisation staff who analysed the data were all masked to the treatment assignments. Both trials are registered withClinicalTrials.gov, numbersNCT02160899 andNCT02414594 . Findings: From June 25, 2014, to Nov 18, 2015, we enrolled 64 participants to the phase 2 trial (51 in cohort A and 13 in cohort B). 35 were randomly assigned to IONIS-APO(a)Rx and 29 to placebo. At day 85/99, participants assigned to IONIS-APO(a)Rx had mean Lp(a) reductions of 66·8% (SD 20·6) in cohort A and 71·6% (13·0) in cohort B (both p<0·0001 vs pooled placebo). From April 15, 2015, to Jan 11, 2016, we enrolled 58 healthy volunteers to the phase 1/2a trial of IONIS-APO(a)-LRx . Of 28 participants in the single-ascending-dose phase, three were randomly assigned to 10 mg, three to 20 mg, three to 40 mg, six to 80 mg, six to 120 mg, and seven to placebo. Of 30 participants in the multiple-ascending-dose phase, eight were randomly assigned to 10 mg, eight to 20 mg, eight to 40 mg, and six to placebo. Significant dose-dependent reductions in mean Lp(a) concentrations were noted in all single-dose IONIS-APO(a)-LRx groups at day 30. In the multidose groups, IONIS-APO(a)-LRx resulted in mean reductions in Lp(a) of 66% (SD 21·8) in the 10 mg group, 80% (SD 13·7%) in the 20 mg group, and 92% (6·5) in the 40 mg group (p=0·0007 for all vs placebo) at day 36. Both antisense oligonucleotides were safe. There were two serious adverse events (myocardial infarctions) in the IONIS-APO(a)Rx phase 2 trial, one in the IONIS-APO(a)Rx and one in the placebo group, but neither were thought to be treatment related. 12% of injections with IONIS-APO(a)Rx were associated with injection-site reactions. IONIS-APO(a)-LRx was associated with no injection-site reactions. Interpretation: IONIS-APO(a)-LRx is a novel, tolerable, potent therapy to reduce Lp(a) concentrations. IONIS-APO(a)-LRx might mitigate Lp(a)-mediated cardiovascular risk and is being developed for patients with elevated Lp(a) concentrations with existing cardiovascular disease or calcific aortic valve stenosis. Funding: Ionis Pharmaceuticals.